Do shoot anatomical characteristics allow rice to grow well under water deficit?. (17th June 2021) - Ouyang, Wenjing; Yin, Xinyou; Yang, Jianchang; Struik, Paul C.
Abstract: Increasing fresh water scarcity is a major constraint for rice ( Oryza sativa ) productivity under future climatic conditions. It is important to understand why rice cannot perform like other dryland cereals, when grown under drier soil conditions. The responses of plant growth, plant water status, leaf and stem anatomical attributes to soil water deficit were examined at two developmental stages of three rice and two wheat ( Triticum aestivum ) cultivars grown under three water regimes in a pot experiment. Yield and yield components were determined at plant maturity. The stress sensitivity of plant growth was slightly more prominent at vegetative than at flowering stages. Water deficit limited root growth but had little impact on above‐ground growth in rice plants. The xylem system of the leaves was more developed in rice than in wheat, but the opposite was true for the root xylem system. Compared with stem xylem attributes, leaf xylem attributes played a larger role in modulating leaf water potential under water deficit. In addition, the variation in yield response to water deficit between various types of rice, and between rice and wheat was closely associated with the response of leaf water potential to water deficit. To grow rice in drier conditions, its xylem system should be balanced by increasing root growth and modifying leaf anatomy.